2014
DOI: 10.1128/aac.01958-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Differential Quinolone Susceptibility of Mycobacterial DNA Gyrase

Abstract: b DNA gyrase is a type II topoisomerase that catalyzes the introduction of negative supercoils in the genomes of eubacteria. Fluoroquinolones (FQs), successful as drugs clinically, target the enzyme to trap the gyrase-DNA complex, leading to the accumulation of double-strand breaks in the genome. Mycobacteria are less susceptible to commonly used FQs. However, an 8-methoxysubstituted FQ, moxifloxacin (MFX), is a potent antimycobacterial, and a higher susceptibility of mycobacterial gyrase to MFX has been demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Moxifloxacin is a well-known type II topoisomerase poison which targets mycobacterial DNA gyrase (40,41). The experiments described above indicated that imipramine poisons the topoI reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Moxifloxacin is a well-known type II topoisomerase poison which targets mycobacterial DNA gyrase (40,41). The experiments described above indicated that imipramine poisons the topoI reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In GyrA, a noncatalytic Mg 2þ ion coordinated with four water molecules appears as a bridge for hydrogen bonding between quinolone and Ser83 and Asp87 (Wohlkonig et al 2010), the two most commonly mutated amino acids in quinolone-resistant mutants. Although quinolones can bind to mycobacterial gyrase in the absence of DNA (Kumar et al 2014), in E. coli, the gyrase -DNA complex shows increases in the amount and specificity of quinolone binding relative to gyrase alone (Shen et al 1989;Willmott and Maxwell 1993).…”
Section: Quinolone Mechanism Of Actionmentioning
confidence: 99%
“…Both compounds inhibited S. pneumoniae TopoI activity in vitro at concentrations equivalent to those necessary to inhibit bacterial growth (∼10 μM) without affecting human cell viability ( García et al, 2011 ). M. tuberculosis possess two DNA topoisomerases: one type II enzyme, DNA gyrase, which is targeted by fluoroquinolone antibiotics ( Kumar et al, 2014 ) and one type I enzyme, topoisomerase I (MtbTopoI), which is encoded by Rv3646c ( topA ) gene. This gene has been shown to be essential for M. tuberculosis growth ( Kumar et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%